2020
DOI: 10.3390/nu12092858
|View full text |Cite
|
Sign up to set email alerts
|

A National e-Health Program for the Prevention and Management of Overweight and Obesity in Childhood and Adolescence in Greece

Abstract: Obesity in childhood and adolescence represents one of the most challenging public health problems of the 21st century owing to its epidemic proportions worldwide and the associated significant morbidity, mortality and public health costs. In Greece, the prevalence of overweight and obesity in childhood and adolescence exceeds 30–35%. To address the increasing prevalence of overweight and obesity in children and adolescents in our country, we developed the ‘National e-Health Program for the Prevention and Mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…It is characterized by the increased accumulation of body fat, especially visceral adipose tissue. BMI (body weight in kilograms divided by the square of height in meters) is used as the standard clinical measure of overweight and obesity, although it has limitations when it is applied for muscular subjects, given that it cannot distinguish between lean and fat mass and fat mass distribution [8,9]. According to WHO, for adults, overweight corresponds to a BMI between 25-30 kg/m 2 and obesity to a BMI > 30 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is characterized by the increased accumulation of body fat, especially visceral adipose tissue. BMI (body weight in kilograms divided by the square of height in meters) is used as the standard clinical measure of overweight and obesity, although it has limitations when it is applied for muscular subjects, given that it cannot distinguish between lean and fat mass and fat mass distribution [8,9]. According to WHO, for adults, overweight corresponds to a BMI between 25-30 kg/m 2 and obesity to a BMI > 30 kg/m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the early implementation of multidisciplinary personalized intervention programs for the prevention and management of overweight and obesity in childhood and adolescence is imperative. Several lifestyle intervention strategies have been proposed, which mostly involve a healthy lifestyle of diet, sleep and physical activity [ 7 , 8 , 9 ]. In addition, novel e-health applications have been developed to address the epidemic of childhood obesity [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Five hundred and eight (n total = 508; 239 males, 269 females) children and adolescents, aged 10.14 ± 0.13 years (mean ± SE), consecutively attending our Out-patient Clinic for the Prevention and Management of Overweight and Obesity in Childhood and Adolescence were recruited to participate in the study. All participants were evaluated by a Pediatrician, Pediatric Endocrinologist, Pediatric Dietician, a professional fitness Personal Trainer and—when necessary—a Pediatric Clinical Psychologist, and entered a personalized, comprehensive, multidisciplinary management intervention program that provided personalized advice and guidance on healthy diet and physical exercise to participants and their families [ 13 , 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is imperative that the prevention and management of overweight and obesity should commence in childhood to ensure improved health in adulthood, as well as reduced medical costs owing to complications of obesity. To address the epidemic of childhood obesity in our country, we developed novel e-Health applications that are expected to play an important role in the prevention and management of overweight and obesity in children and adolescents [ 12 , 13 ]. In addition, we demonstrated that a structured, comprehensive, multidisciplinary intervention program that provides detailed and individualized advice on diet and exercise are effective at reducing the prevalence of overweight and obesity in childhood and adolescence [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding use of e-health programs, two papers by Tragomalou et al, a review and an intervention study, revealed the effectiveness of these programs on both prevention and treatment of cardiometabolic risk factors. Specifically, the intervention study of Tragomalou et al, which used an electronic personalized nutrition program in overweight and obese children and adolescents and their families, showed that after one year of intervention, the study participants significantly reduced their body weight and other cardiometabolic risk factors, such as their glycosylated hemoglobin (HBA1) [ 23 , 24 ].…”
mentioning
confidence: 99%